Clinical profile, inhaler technique, and predictors of inhaler adherence among asthma and COPD patients who attended the outpatient emergency department for acute exacerbation - Koh, Hock Peng; Teoh, Paula Suen Suen; Roslan, Nurul Liana (Internal and emergency medicine, 2025)
Understanding the patients’ clinical profile, barriers to optimal inhaler use, and adherence are crucial in achieving the treatment goal for asthma and chronic obstructive pulmonary disease (COPD). This study aimed to assess the inhaler technique and identify the predictors of inhaler adherence among asthma and COPD patients who presented to the Emergency Department (ED). This prospective cross-sectional study recruited patients who presented to the outpatient ED of a tertiary hospital for mild-to-moderate exacerbation from March 2022 to February 2023. Convenience sampling was used in this study. The inhaler techniques and adherence of all subjects were evaluated. Regression analysis was used to identify predictors of inhaler adherence. We recruited 120 subjects with a mean age of 47.8 ± 16.0 and were predominantly asthma patients ( n = 85, 70.8%). Most were on regular follow-up ( n = 72, 60.0%) and adhered to their inhaler(s) ( n = 86, 71.7%). Less than half of the subjects use their inhaler(s) correctly ( n = 45, 37.5%). Three predictors of inhaler adherence were identified: regular follow-up (aOR 2.072, p = 0.041), correct inhaler technique (aOR 3.071, p = 0.039), and ability to explain inhalers’ mode of action (aOR 10.906, p = 0.031). The high rate of wrong inhaler techniques among asthma and COPD patients is worrisome. Identified predictors of inhaler adherence should be targeted when managing this group of patients. In addition to the exacerbation treatment in the ED, referrals to public primary health clinics for regular follow-ups, evaluation of inhaler techniques, and counseling to enhance patient knowledge are crucial.